삽화 구성을 통한 관용어 읽기지도가 인공와우 착용 청각장애학생의 관용어 이해와 쓰기에 미치는 효과 - 김영익(Yeong Ik Kim); 남윤석(Yun Seok Nam); 권순우(Soon Woo Kwon) (언어치료연구, 2012)
본 연구는 삽화 구성을 통한 관용어 읽기지도가 인공와우 착용을 한 학령기 이후 청각장애학생의 관용어 이해와 쓰기에 미치는 효과에 대하여 살펴보았다. 청각장애학생들은 영․유아기 때부터 청력손실로 인해 언어발달에 지체를 보이고, 차후 학교생활에 있어서도 읽기와 쓰기에 어려움을 가지게 된다. 나아가 성인이 되어 청인들과 의사소통 상황에서 비유적, 또는 은유적 표현으로 사용되어지는 관용어와 속담, 사자성어 등의 이해와 표현에 상당한 좌절감을 가지게 된다. 따라서 청각장애학생의 특성 이해를 바탕으로 잔존능력인 시각 정보 채널을 활용한 삽화 구성 자료를 제시하여 이해와 쓰기에 대한 동기를 부여하고 흥미를 이끌어 내는 지도 방법으로 관용어 이해와 쓰기에 도움을 주고자 하였다. 학령기 이후 중․고등부 청각장애학생 3명을 선정 대상자간 중다기초선 설계를 사용하여 주 2회 총 26～32회기 중재시간은 1회기에 40～45분 실시하였다. 연구 결과는 다음과 같다. 첫째, 삽화 구성을 통한 관용어 읽기지도는 청각장애학생 대상자 3명 모두 관용어 이해능력의 향상에 효과적이었다. 둘째, 삽화 구성을 통한 관용어 읽기지도는 청각장애학생 대상자 3명 모두 관용어 쓰기능력의 향상에 효과적이었다. 셋째, 삽화 구성을 통한 관용어 읽기지도는 대상자 3명 모두 이해능력에서의 성취율 범위가 쓰기능력에 대한 성취율 범위 보다 높았다. 넷째, 삽화 구성을 통한 관용어 읽기지도는 중재가 끝난 후에도 대상자 3명 모두 유지에 효과적이었다. 따라서 이러한 결과들을 고려해보면, 삽화구성을 통한 관용어 읽기지도가 이 연구의 대상인 청각장애학생에게 효과적인 것으로 결론을 내릴 수 있다. This study was designed to investigate the effect of idiom reading instruction by illustrated configurations on the idiom understanding and writing of hearing impaired students who passed school age and had cochlear implants. Typically these students are retarded in language development because of hearing impairment from the beginning of infancy, which leads to difficulty in reading and writing when they attend school. In addition, they have difficulty in understanding idioms, proverbs, or four-character Chinese idioms which have figurative or metaphorical expressions. This difficultly leads to further difficulties in having conversations, which in turn leads to frustration. In light of this, this study used the remaining visual information channel to help students become interested in the understanding and writing of idioms by materials with illustrated configurations. Three hearing impaired students who attended middle and high school were selected for this study, and they were provided, based on the multiple-baseline design across, with 26 to 32 sessions of 40 to 45 minutes. The findings are summarized as follows: First, the idiom reading instruction by illustrated configurations had effect on all the students' understanding ability of idioms. Second, the idiom reading instruction by illustrated configurations had effects on all the students' writing ability. Third, the idiom reading instruction by illustrated configurations had more effect on all the students' understanding achievements than their writing. Fourth, the effect of the idiom reading instruction by illustrated configurations remained for all students even after the sessions were finished. In conclusion, this suggests that the idiom reading instruction by illustrated configurations are effective on hearing impaired students. KCI Citation Count: 7